PENGARUH JARAK TANAM DAN PUPUK ANORGANIK TERHADAP BIOMASA, KLOROFIL, DAN KADAR AIR RELATIF DAUN BAWANG MERAH FASE VEGETATIF - Rajiman, Rajiman; Megawati, Sari; Anshori, Arif; Martini, Tri (Fakultas Pertanian, Universitas Janabadra, 2024)
The aim of this study was to study the effect of plant spacing and variations of inorganic fertilizers on the biomass, chlorophyll, and relative moisture content of shallots in the vegetative growth phase. The research was conducted in May–June 2023 in Plembuatan Village, Playen District, Gunungkidul Regency, D.I. Yogyakarta. The study used a Complete Factorial Randomized Block Design with 3 replications. The first factor is the spacing (J), consisting of: J1 = 10x10 cm2, J2 = 10x15 cm2, J3 = 10x20 cm2, and J4 = 15x15 cm2. The second factor is the variation of inorganic fertilizers consisting of: N1 = basic fertilize of NPK Phonska r 250 kg/ha, SP-36 150 kg/ha, follow-up I and II NPK Phonska 75 kg/ha, N2 = basic fertilizer of NPK Phonska 250 kg/ha, SP -36 150 kg/ha, follow-up I and II urea 25 kg/ha, N3 = basic fertilizer of NPK Phonska 400 kg/ha, SP-36 150 kg/ha, follow-up I and II urea 25 kg/ha, and N4 = basic fertilizer of NPK phonska 250 kg/ha, SP-36 150 kg/ha, follow-up I and II urea 25 kg/ha and KCl 18.75 kg/ha. The results showed that the spacing treatment and fertilizer variation significantly interacted with the parameters of plant height, number of leaves, oven dry weight per clump, chlorophyll a content, chlorophyll b content, total chlorophyll content and relative moisture content of leaf aged 4 WAP, but did not significantly interact with fresh weight per clump. The increase in plant spacing and variations in inorganic fertilizers did not significantly affect plant height, number of leaves and wet weight per clump. Keywords: Biomass, Chlorophyll, and Inorganic Fertilizers INTISARIPenelitian bertujuan mengetahui pengaruh jarak tanam dan variasi pupuk anorganik terhadap biomasa, klorofil, dan kadar air relatif daun bawang merah pada fase pertumbuhan vegetatif. Penelitian dilaksanakan bulan Mei–Juni 2023 di Desa Plembuatan, Kapanewon Playen, Kabupaten Gunungkidul, Provinsi D.I. Yogyakarta. Penelitian menggunakan Rancangan Acak Kelompok Lengkap Faktorial dengan 3 ulangan. Faktor pertama jarak tanam (J), terdiri : J1 = 10x10 cm2, J2 = 10x15 cm2, J3 =10x20 cm2, dan J4 = 15x15 cm2. Faktor kedua variasi pupuk anorganik terdiri : N1 = Pupuk dasar NPK phonska 250 kg/ha, SP-36 150 kg/ha, susulan I dan II NPK Phonska 75 kg/ha, N2 = Pupuk dasar NPK phonska 250 kg/ha, SP-36 150 kg/ha, susulan I dan II urea 25 kg/ha, N3 = Pupuk dasar NPK phonska 400 kg/ha, SP-36 150 kg/ha, susulan I dan II urea 25 kg/ha, dan N4 = Pupuk dasar NPK phonska 250 kg/ha, SP-36 150 kg/ha, susulan I dan II urea 25 kg/ha dan KCl 18,75 kg/ha. Hasil penelitian menghasilkan perlakuan jarak tanam dan variasi pupuk nyata berinteraksi terhadap parameter tinggi tanaman, jumlah daun, bobot kering oven per rumpun, kandungan klorofil a, kandungan klorofil b, kandungan klorofil total dan kadar air relatif daun bawang umur 4 MST, tetapi tidak nyata berinteraksi terhadap bobot basah per rumpun. Peningkatan jarak tanam maupun variasi pupuk anorganik tidak nyata mempengaruhi tinggi tanaman, jumlah daun dan bobot basah per rumpun. Kata Kunci : Biomasa, Klorofil, dan Pupuk Anorganik.